Controle da jurisdição do árbitro pelo Poder Judiciário antes da sentença arbitral no direito brasileiro - Ramos, Caio Pazinato Gregório (2019)
The present study aims to analyze the possibility of court inquiry into arbitral jurisdiction prior to the rendering of the arbitral award under Brazilian law. Initially, we analyze the competence-competence rule as the starting point for the study of the judicial control over the arbitrator’s jurisdiction, focusing on its main aspects, such as its legal source, the applicable law, its positive and negative effects and other legal mechanisms of arbitration law that, alongside the competence-competence rule, are relevant for the analysis of practical problems. After that, we conduct a comparative law analysis, with the purpose of studying the different existing models of competence-competence and, as a next step, comparing them to Brazilian law. The conclusion reached through such analysis is that Brazilian law establishes, as a general rule, a priority in favor of the arbitrator to decide upon its jurisdiction, leaving court control to a posterior moment. Nonetheless, pursuant to the reasoning developed during the course of this work, we defend the possibility of premature court inquiry into arbitral jurisdiction, provided that it occurs solely in relation to issues verifiable plainly, by means of a prima facie analysis, without the need of an evidentiary stage, on a summary basis. Finally, we analyze the procedural mechanisms that may be used for the purposes of such control, as well as the elements that, as component parts of the arbitral jurisdiction, could be analyzed by national courts when deciding upon arbitral jurisdiction in the pre-award stage